A Non Platinum Regimen for the Treatment of Recurrent or Metastatic Squamous Cell Carcinoma of the Head and Neck Region. Results From an Extended Phase II Study With Paclitaxel and Capecitabine - Bentzen, Jens K. D.; Kristensen, Claus Andrup; Overgaard, Marie; Rytter, Carsten; Jensen, Kenneth; Hansen, Hanne Sand (Frontiers in Oncology, 2018)
Background This study presents the results of an extended phase II study originally published in 2007, regarding the antitumor activity and toxicity of a non-platinum containing regimen with paclitaxel and capecitabine for the treatment of recurrent or disseminated squamous cell carcinoma of the head and neck region. Fifty patients were included in the original study. Materials and methods A total of 183 patients with recurrent or disseminated squamous cell carcinoma were eventually included in the extended study. There were 37 women and 146 men. The mean age was 56 years. Performance status (WHO) was as follows: WHO 0:31, WHO 1:107, and WHO 2:45 patients. The treatment consisted of paclitaxel 175 mg/m2, once every third week and capecitabine 825 mg/m2 p.o. b.i.d for 2 weeks. Results The overall response rate (complete response and partial response) according to the WHO criteria was: 33% (CI 26–40). The median progression-free survival was 4.8 (CI 4.2–5.4) months. The median overall survival (OS) was 8.9 (CI 7.6–9.5) months. Compliance was good. Of the 1,131 cycles, only 13% had to be administered with a reduced dose and/or postponed to a later date. Toxicity was mild and grades 3 and 4 toxicities were uncommon. Two toxic deaths were registered though. Conclusion The response rate and the OS for this low toxicity regimen makes it a feasible alternative for not cisplatin eligible patients.